The impact of aesthetic medicine procedures on patient comfort in life, physical activity and mental health - Karwańska, Aleksandra; Kulbat, Aleksandra; Matyka, Kamila; Uniłowska, Izabela; Kojder, Ewa; Dolenha, Arsen; Dovzhuk, Yuliia; Ochał, Justyna; Ferschke, Anna; Szymczyk, Aleksandra (Journal of Education, Health and Sport, 2023)
Introduction Aesthetic medicine procedures significantly affect the comfort of patient’s lives, their amount of physical activity and mental health. Today, medicine serves not only to eliminate the consequences of diseases or their prevention, but also aesthetic considerations, which are directly related to the quality of life in general. Purpose The purpose of this review is to present the current state of knowledge on the impact of aesthetic medicine procedures on the comfort of patients’ lives. Methods Literature was searched in PubMed and Google Scholarship databases. Publicly available books were searched. Results People who use aesthetic medicine can improve their self-esteem and even their socioeconomic status or get a better job than before. Conclusions Patients’s quality of life and mental health significantly increase after aesthetic medicine procedures.